Réponses

2013-11-02T11:49:23+01:00
3x+6=3(x+2)

(x+1)(x+5)+7(x+1)=(x+1)(x+5+7)=(x+1)(x+12)

(x+1)(3x+4)+(x+1)(x-3)=(x+1)(3x+4+x-3)=(x+1)(4x+1)

(x+1)(2x+3)-(x-7)(x+1)=(x+1)(2x+3-x+7)=(x+1)(x+10)

x^2-10x+25=(x-5)^2

36x^2+24x+4=(6x+2)^2

(x+1)(2x+1)+3(x+1)(x+8)=(x+1)(2x+1+3(x+8))=(x+1)(2x+1+3x+24)=(x+1)(5x+25)=5(x+1)(x+5)

64-9x^2=(8-3x)(8+3x)

7(x+4)(x+1)-(3x-4)(x+1)=(x+1)(7(x+4)-3x+4)=(x+1)(7x+28-3x+4)=(x+1)(4x+32)=4(x+1)(x+8)

(3x-1)^2-16=(3x-1-4)(3x-1+4)=(3x-5)(3x+3)=3(3x-5)(x+1)

Les niveaux 5,6,8 et 10 sont des identités remarquables